Barriers to participation in the social economy in Greece - Tsompanoglu, Geōrgios Od. (Oñati Socio-Legal Series, 2012)
The current crisis in Greece, an EU member for over 30 years, has brought to the surface the character of the Greek politico-administrative system as it handles employment, migration and associated forms of social protection. Similarly, recent attempts at legislative reforms of the operation of social economy enterprises have yet to be implemented, while the current legislation governing them, i.e. as Foundations, dates back to ...1939. The difficulties in recognising and regulating the social economy sector seem to emanate from the organisation of the overall employment security system in place. The employment relationship seems to be embedded within a bifurcated system of labour whereby the employment relationship is secure only in the public sector while the private sector is controlled by a precarious system of labour security, a separate health system and with its own political organisation. The lack of a unified national labour system does not allow the formation of a national system of employment (qualifications) and, hence, a way to overcome nepotism and the political (party) patronage system which defines, in a determining way, labour relations. This division is maintained by the politico-administrative labour regime put in place, under the extra-ordinary political situation that emerged after World War II (WWII). The paper explores this hidden reality defining the organisation of the employment system in Greece, its politico-administrative controls that seem to aim at ‘arresting’ the emergence of a social economy. This leads to a hidden social economy of a fragmented private labour market, which is regulated separately from the secure “public” employment sector. This rather anachronistic and discriminatory system of political order of labour divides workers in Greece.